2016
DOI: 10.1093/hmg/ddw186
|View full text |Cite|
|
Sign up to set email alerts
|

A recurrent p.Arg92Trp variant in steroidogenic factor-1 (NR5A1) can act as a molecular switch in human sex development

Abstract: Cell lineages of the early human gonad commit to one of the two mutually antagonistic organogenetic fates, the testis or the ovary. Some individuals with a 46,XX karyotype develop testes or ovotestes (testicular or ovotesticular disorder of sex development; TDSD/OTDSD), due to the presence of the testis-determining gene, SRY. Other rare complex syndromic forms of TDSD/OTDSD are associated with mutations in pro-ovarian genes that repress testis development (e.g. WNT4); however, the genetic cause of the more com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 29 publications
6
104
0
3
Order By: Relevance
“…In the XY gonad the activation of SRY expression, possibly initiated by CBX2/WT1/GATA4/FOG2/ NR5A1, leads to the upregulation of Sox9 expression via a synergy with Nr5a1 at a Sox9 enhancer such as Tesco [Sekido and LovellBadge, 2008]. In the XX gonad the supporting cell precursors accumulate β-catenin in response to RSPO1/WNT4 signaling, which either directly or indirectly represses SOX9 expression, perhaps at least in human, by interacting with NR5A1 [Bashamboo et al, 2016]. Once Sox9 levels reach a critical threshold, several positive regulatory loops are initiated, including autoregulation of its own expression and formation of feed-forward loops via FGF9 or PGD2 signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the XY gonad the activation of SRY expression, possibly initiated by CBX2/WT1/GATA4/FOG2/ NR5A1, leads to the upregulation of Sox9 expression via a synergy with Nr5a1 at a Sox9 enhancer such as Tesco [Sekido and LovellBadge, 2008]. In the XX gonad the supporting cell precursors accumulate β-catenin in response to RSPO1/WNT4 signaling, which either directly or indirectly represses SOX9 expression, perhaps at least in human, by interacting with NR5A1 [Bashamboo et al, 2016]. Once Sox9 levels reach a critical threshold, several positive regulatory loops are initiated, including autoregulation of its own expression and formation of feed-forward loops via FGF9 or PGD2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This view was supported by our screen of further 40 cases of 46,XX DSD that did not reveal any other NR5A1 mutations. In 2015, we were contacted by different groups who had also identified the same NR5A1 p.Arg92Trp mutation in association with 46,XX testicular DSD [Bashamboo et al, 2016]. Two families had a single affected child who carried a de novo NR5A1 p.Arg92Trp mutation, and this formally excluded a founder mutation.…”
Section: Nr5a1 Parg92trp and 46xx Dsdmentioning
confidence: 99%
“…The spectrum of disorders associated with NR5A1 variants in 46,XX individuals was further expanded by the demonstration of the specific recurrent heterozygous p.Arg92Trp NR5A1 variant, in association with variable degrees of testis development in 46,XX patients from unrelated families (Baetens et al, 2016; Bashamboo et al, 2016; Igarashi et al, 2017). The p.Arg92Trp NR5A1 mutation was described in ten SRY negative 46,XX DSD patients, six with testicular DSD and four with ovotesticular DSD.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro assays demonstrated that the p.Arg92Trp mutant lost its binding capacity to a consensus NR5A1 response element and reduced activation of some minimal promoters ( Amh, Cyp11a1 ) (Bashamboo et al, 2016). This mutated protein was also less sensitive to NR0B1‐induced suppression on the SOX9 TESCO element, leading to testis formation (Igarashi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypes ranged from ambiguous genitalia, to penoscrotal hypospadias, to micropenis noted at birth, to small testes and low testosterone noted in adolescence. Of note, one proband had a sibling with labial fusion, clitoral enlargement, and dysgenetic testes in the inguinal region who was found to have a 46,XY karyotype and the same NR5A1 mutation [23]*.…”
Section: A Role For Nr5a1 In Ovarian Fate Specificationmentioning
confidence: 99%